Izin Usaha Pemanfaatan Satwa Liar Di Indonesia - Yahya, Ivan Fairul (Jurnal sosial dan sains, 2025)
The use of wildlife in Indonesia has an important role in biodiversity conservation and natural resource-based economic development. However, the practice of its use must be strictly controlled through legal and sustainable licensing. This study aims to analyze regulations, procedures, and challenges in the implementation of Wildlife Utilization Business Licenses (IUPS) in Indonesia. With a normative juridical approach and case studies on several business actors, it was found that although regulations have been regulated through the Regulation of the Minister of Environment and Forestry, their implementation still faces obstacles such as weak supervision, illegal licensing practices, and lack of coordination between agencies. In addition, there is an inequality between conservation interests and economic needs that require more adaptive and ecosystem-based policies. This study suggests the need to reformulate licensing policies, increase law enforcement capacity, and strengthen monitoring systems as an effort to realize sustainable and responsible wildlife utilization.